Globalization, Internationalization, and the Recruitment of International Students in Higher Education, and in the Ontario Colleges of Applied Arts and Technology - Cudmore, Geoffrey (Canadian Journal of Higher Education, 2005)
This paper explores general issues relating to globalization and higher education; the internationalization of higher education, and particularly the recruitment of international students. This subject is examined through a range of topics around the global development of the market approach to the recruitment of international students and a focus on the current situation regarding the recruitment of international students in the Colleges of Applied Arts and Technology in Ontario (CAATs). As the number of international students seeking educational opportunities grows to 7 million over the next 20 years, the ability of the CAATs, the Canadian educational system, and the governments of Ontario and Canada to market the welcoming and safe multicultural Canadian experience, and the excellence of the educational offerings and opportunities in CAATs to potential international students will, in great measure, determine their success and their survival in an increasingly globalized world.